2014
DOI: 10.1080/03601277.2014.899830
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reminiscence Therapy on Depression, Quality of Life, Ego-Integrity, Social Behavior Function, and Activies of Daily Living in Elderly Patients With Mild Dementia

Abstract: This study investigated the effects of reminiscence therapy work on depression, quality of life, ego-integrity, social behavior function, and activities of daily living. This study was a quasiexperimental study using a single-group pretest=posttest design. This therapy consists of eight sessions of 2.5 hours with a specific theme. A total of 19 patients with mild dementia who registered at a mental health center in community-dwelling participated in this study. Hypotheses were supported by quality of life, ego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 33 publications
(20 reference statements)
2
36
0
Order By: Relevance
“…Wingbermuehle et al (2014) also describe reminiscence as a successful approach to improving the quality of life of people with mild to moderately severe dementia. Jo and Eunju (2015) in their study on reminiscence work with patients with dementia and their quality of life and assess reminiscence as beneficial, as it improves communication in connection with the opportunity it provides to look back on their lives. The effect on communication was not tested in our research, but it was clear that the stimulation of speaking in group meetings, and the subsequent sharing of experiences were the cause of the development of communication among elderly adults, and also between elderly adults and staff.…”
Section: Discussionmentioning
confidence: 99%
“…Wingbermuehle et al (2014) also describe reminiscence as a successful approach to improving the quality of life of people with mild to moderately severe dementia. Jo and Eunju (2015) in their study on reminiscence work with patients with dementia and their quality of life and assess reminiscence as beneficial, as it improves communication in connection with the opportunity it provides to look back on their lives. The effect on communication was not tested in our research, but it was clear that the stimulation of speaking in group meetings, and the subsequent sharing of experiences were the cause of the development of communication among elderly adults, and also between elderly adults and staff.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses usually employ reminiscence in geriatric and dementia care settings to improve neuropsychiatric symptoms and promote a sense of life satisfaction, pleasure, and well‐being for patients with mild dementia . Reminiscence is a stimulating activity that nurses use to promote patients’ development of communication skills and reduce social isolation through social interaction and connecting with others . During reminiscence sessions, reminiscence practitioners provide patients with a fertile ground for improving social inclusion and a comfortable atmosphere in which they can vent about stressful situations in their lives .…”
Section: Resultsmentioning
confidence: 99%
“…The current concept analysis explains the importance that additional research holds for the further development of the reminiscence concept and provides the next step for establishing reminiscence as a more widespread and accessible intervention in mild dementia care. Based on the results of this analysis, reminiscence can be adopted as an independent nursing intervention, as its defining attributes make it effectively geared towards nursing intervention . The close patient‐nurse relationships afforded by the nature of dementia care may allow nurses to use their knowledge of the environment, the individual patients, and effective therapeutic techniques in constructing comprehensive reminiscence activities .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through incorporating digital somatosensory games into reminiscence therapy, the researchers effectively enhanced users' healthy daily living activities and intergenerational interactions within their families, thereby generating positive perceptions. Jo et al [2] indicated that reminiscence therapy not only decelerates physiological and psychological deterioration caused by aging but also enables elderly people to engage in interpersonal and social interactions through positive and active approaches. Through doing so, it improves their social behaviors and interpersonal relationships as well as delaying the regression of their cognitive, verbal, and communication skills.…”
Section: Introductionmentioning
confidence: 99%